From Frances Sheridan’s A Trip to Bath (1765) to Elizabeth Kuti’s The Whisperers (1999): Questions of Genre, Adaptation Strategies and Authorship - Kurdi, Mária (FOCUS: Papers in English Literary and Cultural Studies, 2024)
The English-Hungarian Elizabeth Kuti’s (1969-) comedy, The Whisperers (1998) is based on the Anglo-Irish Frances Sheridan’s (1724-1766) unfinished third play, A Trip to Bath (1765). In fact, the later work is a special adaptation of the earlier one, the result of an intertextual conversation between the two writers, with Kuti completing Sheridan’s fragment in the spirit of the original. This essay examines how A Trip to Bath fits in with the contemporary comic genre on the stage and the ways and modes in which The Whisperers recasts it to produce a unique piece of collaborative theater. Kuti’s addition continues and energizes the reflection of the social and emotional variedness in the co-authored work, a feature which characterizes the best of eighteenth-century English comedy. The argument of the essay also concerns itself with issues of dual authorship, adaptation strategies, and both textual and dramaturgical coherence in the newly produced work.